2021
DOI: 10.7554/elife.67065
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for differential recruitment of orbitostriatal transmission during actions and outcomes following chronic alcohol exposure

Abstract: Psychiatric disease often produces symptoms that have divergent effects on neural activity. For example, in drug dependence, dysfunctional value-based decision-making and compulsive-like actions have been linked to hypo- and hyper-activity of orbital frontal cortex (OFC)-basal ganglia circuits, respectively, however, the underlying mechanisms are unknown. Here we show that alcohol exposed mice have enhanced activity in OFC terminals in dorsal striatum (OFC-DS) associated with actions, but reduced activity of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 94 publications
2
22
0
Order By: Relevance
“…It is notable that, within the context of “gold standard” behavioral treatments (e.g., exposure with response prevention), similar opposing patterns for acute (increased urges/anxiety) versus long-term (improved CBs, anxiety relief) outcomes are fully expected, and, indeed, an enhanced acute degree of distress-inducing challenge or “exercise” for resisting compulsive urges is considered critical for enduring therapeutic outcomes. The present RSFC findings suggest that acutely down-regulating right lateral OFC-based circuitry may represent a key neural mechanism supporting the adaptive transition from habit-driven (i.e., driven by short-term anxiety/urge relief) to goal-driven adaptive function, consistent with circuit-based animal stimulation studies in which lateral OFC-striatal circuits have been implicated in expression of compulsive-like behaviors (Pascoli et al, 2015, 2018; Renteria et al, 2021).…”
Section: Discussionsupporting
confidence: 83%
“…It is notable that, within the context of “gold standard” behavioral treatments (e.g., exposure with response prevention), similar opposing patterns for acute (increased urges/anxiety) versus long-term (improved CBs, anxiety relief) outcomes are fully expected, and, indeed, an enhanced acute degree of distress-inducing challenge or “exercise” for resisting compulsive urges is considered critical for enduring therapeutic outcomes. The present RSFC findings suggest that acutely down-regulating right lateral OFC-based circuitry may represent a key neural mechanism supporting the adaptive transition from habit-driven (i.e., driven by short-term anxiety/urge relief) to goal-driven adaptive function, consistent with circuit-based animal stimulation studies in which lateral OFC-striatal circuits have been implicated in expression of compulsive-like behaviors (Pascoli et al, 2015, 2018; Renteria et al, 2021).…”
Section: Discussionsupporting
confidence: 83%
“…MC4Rs, like D1Rs, are positively coupled to the cAMP second messenger cascade 18 , 39 , and thus can enhance D1R function 40 . D1R stimulation is necessary for learning new skills 6 , and D1R+MSNs in the DMS is involved in the development of goal-directed action strategies 10 – a process that requires inhibiting unproductive behaviors – and recalling memories linking actions and outcomes 41 . Mc4r -null mice are delayed in learning to nose poke for food, and restoration of MC4R in D1R-containing cells reinstates this capacity 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is through retrograde signaling mediated by endocannabinoids. Supporting this hypothesis, previous studies have shown that deletion of cannabinoid type 1 receptor in OFC → DS projections disrupts the shift from goal-directed to habitual behaviors in mice (Gremel et al, 2016), and increased retrograde signaling mediated by endocannabinoid from OFC to D1R-expressing MSNs contributes to decreased OFC → DS transmission after chronic alcohol exposure (Renteria et al, 2021).…”
Section: Discussionmentioning
confidence: 82%